Mechanism of Electron Acceptor Promoting Propionic Acid Transformation in Anaerobic Fermentation - Hongjing Jing; Wenzhe Li; Ming Wang; Hao Jiao; Yong Sun (Energies, 2022)
To improve the conversion efficiency of propionic acid in the post-anaerobic fermentation of biogas slurry, the anaerobic fermentation process using biogas slurry with a high acid content was simulated in an anaerobic reactor at 35 ± 0.5 °C using sodium propionate as the sole substrate. The effects of different electron acceptors (NO3−, SO42− and Fe3+) on propionic acid conversion and the succession of microbial community structures were investigated. The results showed that the experimental group with the electron acceptor NO3− exhibited the best anaerobic fermentation effect, with a maximum propionate removal rate of 94%, which was 36% higher than the control group without an electron acceptor. The maximum methane production rate was 307.6 mL/g COD, an increase of 30% compared with the control group. Thauera, Aquabacterium, Desulfomicrobium, Clostridium_sensu_stricto_1, and other functional microorganisms were all enriched. The dominant functional genes related to redox reactions, such as K03711, K00384, and K03406, were highly enriched in the reactor when Fe3+ and NO3− were added. The study shows that adding an electron acceptor can enhance interactions between microorganisms, achieve efficient propionate conversion, and improve methane production in the system.